Natural zeros of regge residues - Jones,HF; Scadron,MD (Physical Review, 1968)
We discuss the method of Reggeization of invariant amplitudes with particular reference to the kinematic zeros of the residue functions at nonsense points in J and at t=0. The zeros which occur naturally at these points yield in the first case the sense-choosing solution, and in the second case a well-defined scheme, covariant evasion, for satisfying the t=0 conditions on helicity amplitudes. Factorization is automatically satisfied in our method. © 1968 The American Physical Society.